Participatory budgeting in Bogotá, a midway strategy (2020)
Participatory budgets demonstrate a clear effort to establish an exercise that directly involves citizens in defining the rules of the game for cities. However, in Bogotá there is still much to be strengthened in this area. The directly related indicators that refer to a low confidence in the institutions and in the management of the public budget, demonstrate an enormous challenge where participatory budgeting as a strategy that guarantees transparency, can be the best ally. It was possible to analyze that one of the factors that most see in the efficiency of the execution of PB resources are those related to the absence of control, the lack of coordination of the actors and the failures in strategic planning.